GAMBARAN SANITASI KAPAL LAUT DI PELABUHAN KETAPANG DAN PELABUHAN TANJUNG WANGI - Shelviana Mathofani (Kesmas Indonesia, 2023)
In Indonesia, sea transportation is still an alternative choice of solution used to connect people from one island to another. Ketapang Port and Tanjung Wangi Port are 2 ports that are still active today and are very important assets in Banyuwangi Regency. The port serves as a place of crossing from Java to Bali and/or other islands in Indonesia, a place for ships to dock, and a place for loading and unloading goods. Supervision carried out at the time of arrival of the ship aims to prevent the risk factors that cause World Troubled Community Emergency (KMMD). Therefore, this study aims to describe the sanitary conditions of ships at Ketapang Port and Tanjung Wangi Port. This research method is descriptive observative and the sample is taken using a random sampling system. The results showed that all inspected ships (100%) had met the ship sanitation requirements, meaning that all ships had a low risk of disease transmission in ships, so all ships were entitled to receive a ship sanitation certificate renewal letter (SSCEC). ) as well as a license to lean on (COP). In conclusion, all ships that have been inspected have a low risk of disease transmission in ships that can cause a World Troubled Community Emergency (KMMD).